Physical activity in young children at risk for developmental coordination disorder. (8th April 2019) - King‐Dowling, Sara; Kwan, Matthew Y W; Rodriguez, Christine; Missiuna, Cheryl; Timmons, Brian W; Cairney, John
Abstract : Aim: To examine cross‐sectional differences in patterns of daily physical activity accumulation between preschool children at risk for developmental coordination disorder (DCD) compared to typically developing children. Method: In total, 514 children (292 males, 222 females; 4–5y) were recruited as part of the Coordination and Activity Tracking in CHildren (CATCH) study. Motor competence was assessed using the Movement Assessment Battery for Children, Second Edition; children scoring ≤5th centile comprised the probable DCD group (pDCD, n =87), between the 6th and 16th centile were considered to be at risk for DCD (rDCD, n =149), and >16th centile were considered typically developing ( n =278). Seven‐day physical activity was measured using hip‐worn accelerometers. Average daily intensity of activity, frequency, and duration of moderate‐to‐vigorous physical activity (MVPA) bouts, and triaxial activity counts per minute were determined. Results: No differences in daily activity in any intensity or axis of movement were found among the three groups. However, young children with pDCD accumulated their MVPA in slightly shorter bouts compared to typically developing children. Interpretation: Young children at risk for DCD are not yet in an activity deficit. This may be because of the low motor skill demands of play in this age group. Early motor interventions may be able to promote continued physical activity participation in children with DCD. What this paper adds: Preschool children at risk for developmental coordination disorder (DCD) are not less active than their peers. Overall intensity and frequency of daily activity bouts are similar among motor groups. Children with probable DCD accumulate their activity in shorter bouts. What this paper adds: Preschool children at risk for developmental coordination disorder (DCD) are not less active than their peers. Overall intensity and frequency of daily activity bouts are similar among motor groups. Children with probable DCD accumulate their activity in shorter bouts. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Actividad física en niños pequeños con riesgo de trastorno del desarrollo de la coordinación: Objetivo: Examinar por medio de un corte transversal las diferencias en los patrones de actividad física entre los niños en edad preescolar con riesgo de trastorno del desarrollo de la coordinación (TDC) en comparación con niños con un desarrollo típico Método: En total, se reclutaron 514 niños (292 varones, 222 mujeres; de 4 y 5 años) como parte del estudio Coordinación y Seguimiento de Actividad en niños (CATCH). Las capacidades motrices se evaluaron utilizando el test MABC 2 (Movement Assessment Battery for Children). Los niños con puntaje ≤5 percentilo formaron el grupo con TDC probable (pTDC, n = 87), entre percentilos 6 y 16 se consideraron en riesgo de TDC (rTDC, n = 149), y > percentilo 16 se consideraron con desarrollo típico (o normal, n = 278). La actividad física a lo largo de siete días se midió utilizando acelerómetros portados en la cadera. Se determinó la intensidad diaria promedio de la actividad, la frecuencia y la duración de los momentos de actividad física moderada a intensa (MVPA), y los recuentos de actividad triaxial por minuto. Resultados: No se encontraron diferencias en la actividad diaria en ninguna intensidad o eje de movimiento entre los tres grupos. Sin embargo, los niños pequeños con pTDC desarrollaron su MVPA (actividad física moderada a intensa) en episodios ligeramente más cortos en comparación con los niños con un desarrollo típico. Interpretación: Los niños pequeños en riesgo de TDC aún no presentan un déficit de actividad. Esto puede ser debido a las bajas exigencias motrices del juego en este grupo etario. Las intervenciones motoras tempranas pueden promover la participación en actividades físicas de los niños con TDC. Abstract : Atividade física em crianças pequenas com risco de transtorno do desenvolvimento da coordenação: Objetivo: Observar as diferenças transversais nos padrões de acumulação de atividade física diária entre crianças na idade pré‐escolar com risco de transtorno do desenvolvimento da coordenação (TDC) e crianças de desenvolvimento típico. Métodos: Um total de 512 crianças (292 meninos, 222 meninas; de idade entre 4 e 5 anos) foram recrutadas como parte do estudo Acompanhamento da Coordenação e de Atividades de Crianças ( Coordination and Activity Tracking in CHildren ‐ CATCH ). As competências motoras foram avaliadas por meio da Bateria de Avaliação do Movimento para Crianças (Movement Assessment Battery for Children ‐ MABC) segunda edição. Crianças com pontuação abaixo do quinto percentil compunham o provável grupo com TDC (pDDC, n =87), entre o percentil 6 e 16 foram consideradas com risco de DDC (rTDC, n =149), e aquelas com pontuação acima do percentil 16 foram consideradas de desenvolvimento típico ( n =278). A atividade física ao longo de 7 dias foi mensurada utilizando‐se acelerômetros posicionados no quadril. Foram avaliadas a média de intensidade da atividade diária, frequência e duração das atividades físicas moderadas a vigorosas e contagem das atividades triaxiais por minuto. Resultados: Não foram encontradas diferenças entre os três grupos avaliados para intensidade ou eixo de movimento. Entretanto, crianças do grupo pTDC acumularam suas atividades físicas moderadas a vigorosas em blocos ligeiramente mais curtos do que crianças de desenvolvimento típico. Interpretação: Crianças mais novas com risco de TDC ainda não apresentam déficits de atividade física. Isso pode ser devido às baixas demandas motoras de brincar nessa faixa etária. Intervenções motoras precoces podem ser capazes de promover participação em atividades físicas continuada em crianças com TDC.